(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
The aim of this paper is to study the fuzzy connectedness in Raja-Sethupathy- Lakshmivarahan’s sense. Some characterizations and the properties of this type of fuzzy connectedness on fuzzy topological spaces are studied. Interrelationships among fuzzy connectedness are examined. We prove that fuzzy connectedness is preserved under fuzzy continuous mapping. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 175-182, 2017